Corporate Social Responsibility as a Corporate Green Accounting Implementation - Prahara, Rahma Sandhi; A'yuni, Diah Syifaul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The phenomenon of environmental multicrisis occurring today has created a new paradigm of Green Accounting. The concept of Green Accounting directs corporations to make business decisions at an advantage that not only leads to profit orientation but also to the environment and society around the company. Of course, the domino effect of these concerns and considerations is that corporate sacrifices in the form of assets / assets may even be more than that. The role of corporations in supporting Green Accounting is the implementation of Corporate Social Responsibility (CSR). CSR is the moral responsibility of a company to its social, economic, and environmental strategies because of the impact of its operations so that it is expected to contribute benefits to society and the environment. If it is related to Green Accounting, then this will be the right concept to support the 2030 SDGs program.